2003
DOI: 10.1007/s10067-003-0707-4
|View full text |Cite
|
Sign up to set email alerts
|

QT Dispersion in rheumatoid arthritis patients with and without sj�gren's syndrome

Abstract: The aim of this study was to assess the effect of secondary Sjögren's syndrome (SjS) on QT dispersion and corrected QT dispersion in patients with rheumatoid arthritis (RA). We performed electrocardiography and Doppler echocardiography on 58 patients with RA whom we divided into two groups according to the presence of secondary SjS, and on 29 healthy controls. All patients revealed significantly longer QT dispersion and corrected QT dispersion values ( P< 0.05). Diastolic function variables were significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…These results suggest that prolonged QT dispersion could be a useful noninvasive and simple method for the early detection of silent cardiac involvement in SLE patients (11). Moreover, it was also shown that the QT dispersion length is longer in patients with RA than in controls (9,23). RA patients with Sjögren's syndrome (SjS) had more prolonged QT dispersion than in RA patients without SjS, and RA patients with a disease duration of over 5 years also had a more prolonged QT dispersion than those with new onset RA.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These results suggest that prolonged QT dispersion could be a useful noninvasive and simple method for the early detection of silent cardiac involvement in SLE patients (11). Moreover, it was also shown that the QT dispersion length is longer in patients with RA than in controls (9,23). RA patients with Sjögren's syndrome (SjS) had more prolonged QT dispersion than in RA patients without SjS, and RA patients with a disease duration of over 5 years also had a more prolonged QT dispersion than those with new onset RA.…”
Section: Discussionmentioning
confidence: 77%
“…RA patients with Sjögren's syndrome (SjS) had more prolonged QT dispersion than in RA patients without SjS, and RA patients with a disease duration of over 5 years also had a more prolonged QT dispersion than those with new onset RA. This increased QT dispersion was shown as an important predictor of subclinical vascular disease in RA patients (23). Patients with higher QT dispersion also have a higher risk of cardiac death and total mortality (9,23,24).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…13 These alterations include perivascular inflammation, 15 myositis deterioration, malignant disease, 32 left ventricular diastolic dysfunction, 33 interstitial lung disease 34 and death. 32 Sjögren syndrome combined with other autoimmune diseases was associated with increased T-cell activation, 35 Raynaud phenomenon, 36 thyroid disease, 37 cardiac electrical instability 38 and lymphoma, 39 more so than with the respective autoimmune diseases alone. Thus, Sjögren syndrome in dermatomyositis potentially defines a distinct disease subset of dermatomyositis.…”
Section: Discussionmentioning
confidence: 98%
“…табл. 3 и 4) [152][153][154][155][156][157][158]. Увеличение Q-Td при РА ассоциируется с дли-тельностью болезни, приемом ГК, наличием синдрома Шегрена и желудочковых аритмий высоких градаций, что может свидетельствовать о вкладе болезнь-специфических факторов в увеличение риска развития ССО [152][153][154][155].…”
unclassified